#TITLE_ALTERNATIVE# - FAUZI JUWONO ( NIM : 10208058); Pembimbing : Dr. Nurhasan, LUKMAN
Lembang Fault is a geomorphological form which lies in the northern Bandung, West Java, which stretches for 22 km from west to east. Lembang Fault is an active fault which has the potential to cause earthquakes. In this final project, Lembang Fault structure were analyzed based on its resistivity distribution. Magnetotelluric method is used in this final project. The acquisition was carried out by a total of 9 sites on the north-south direction crossing Lembang Fault. From the obtained data, data pre-processing stage can be made that gives information about apparent resistivity and phase for each observation site. Further data processing which includes dimensionality, resistivity curves, as well as modeling and inversion shows Lembang fault which indicated by a significant decrease in resistivity values.